Strategies utilized by teachers to mitigate the face-threatening effects of oral corrective feedback in classroom discussions - Castro, Maria Corazon Saturnina A. (SOSIOHUMANIORA: Jurnal Ilmiah Ilmu Sosial dan Humaniora, 2026)
Corrective feedback is one of the most controversial issues in language teaching. Although corrective feedback is seen as an effective way to improve students’ learning, studies have shown that corrective feedback increases the stress level of students. Corrective feedback is a face-threatening act and this may result in students’ low self-esteem, demotivation, and anxiety. To mitigate the negative impact of corrective feedback , teachers use  strategies and other discourse markers when forming their corrective feedback. This research examined the different kinds of oral corrective feedback (OCF) provided by the teachers and analyzed the  strategies and other discourse markers  the teachers used to mitigate the face-threatening impact of OCF. It examined 128 Student-Teacher Exchanges from five classes. These exchanges were transcribed and analyzed using the frameworks of Lyster and Ranta (1997), Reigel (2005) and Ellis( 2009). The results of the study indicated the teachers’ sensitivity to the emotional/psychological impact  of oral corrective feedback on students and utilized various strategies to mitigate what may be considered embarrassing  or offensive statements of correction.  The data  showed that the teachers employed implicit corrective feedback (similar to off the record politeness strategy), affixed positive markers such as praise markers and other linguistic structures to explicit corrective feedback, and  also utilized larger structures to express positive politeness.